THE IMPACT OF PSYCHOLOGICAL EMPOWERMENT ON THE PERFORMANCE OF THE INTERNAL AUDITOR-A SURVEY STUDY IN THE UNIVERSITIES OF AL-FURAT AL-AWSAT (World Economics and Finance Bulletin, 2025)
The main purpose of this research is to study the role of psychological empowerment in enhancing the performance of the internal auditor in universities located in al-furat al-awsat region. To answer the research questions (What is the degree of practicing psychological empowerment in alfurat al-awsat universities), (Is there a relationship and employees on the performance of the internal auditor in the universities studied), four hypotheses were tested, two branches emanating from two main hypotheses. The research used a sample of (35) individuals from auditors working in the Middle Euphrates universities. The study also used the ready-made statistical packages program (SPSS) to analyze the data. The most important results reached by the research are positive correlation and also a positive effect between variable and the internal auditor performance variable, together and individually, in the universities of the research sample. The study also recommended that the universities studied should delegate the necessary powers to their employees in a way that contributes to providing the necessary independence for employees in universities to enable them to carry out their work quickly and easily and without bureaucratic obstacles.